SHRINKING LUNG SYNDROME IN SYSTEMIC LUPUS ERYTHEMATOSUS-CLINICAL AND THERAPEUTIC CHALLENGES - Reizer, Barbara; Botto, Zofia; Swojnóg, Marzena; Krystek, Klaudia; Felisiak, Patrycja; Kowalczyk, Dominika; Bieszczad, Dominika; Barczewska, Magdalena; Śliwa, Zofia; Ślazyk, Dominik Andrzej (International Journal of Innovative Technologies in Social Science, 2026)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem involvement. One of its rare but clinically significant complications is the shrinking lung syndrome (SLS), which affects less than 1% of patients and presents diagnostic and therapeutic challenges.Aim: This paper aims to present a comprehensive overview of shrinking lung syndrome as a rare manifestation of SLE, with a focus on its pathophysiology, diagnostic difficulties, and current therapeutic approaches.Materials and Methods: A narrative review was conducted based on selected scientific publications indexed in PubMed, Scopus, and Google Scholar. The inclusion criteria included articles describing the pathophysiology, clinical features, diagnosis, and treatment of SLS in the context of SLE.Results: SLS is characterized by progressive dyspnea, diaphragmatic elevation, and restrictive defects on pulmonary function testing. The exact pathogenesis remains unclear but involves neuromuscular dysfunction, diaphragmatic weakness, pleural involvement, and potential autoantibody-mediated mechanisms. Diagnosis is challenging due to the absence of specific markers and requires exclusion of other causes. Treatment primarily includes corticosteroids and immunosuppressants, with adjunctive respiratory rehabilitation. Despite therapy, pulmonary restriction may persist.Conclusions: SLS remains an under-recognized and underdiagnosed complication of SLE. Increased clinical awareness and early diagnostic interventions are key to preventing long-term respiratory impairment. Future research is needed to establish standardized diagnostic protocols and treatment guidelines.